Development and evaluation of a framework to support accountability in Automated Decision-Making (ADM) - Baguley, Kathryn Rebecca (2025)
This PhD uses a mixed methods multidisciplinary approach to assist Small and Medium-sized Organisations (SMOs) in understanding the General Data Protection Regulation (GDPR) and increase their accountability when looking to implement Automated Decision-Making (ADM) technologies. To support SMOs with this task, the PhD develops and evaluates a framework to support accountability from Legal, Ethical and Practical perspectives.